Comparação de desempenho da deconvolução preditiva multicanal e da filtragem f-k na atenuação de múltiplas do fundo do mar - Luz, Marcos Augusto Lima da (2012)
The seismic reflection is used on a large scale in oil exploration. In case of marine acquisition the presence of high impedance contrast at the interfaces water/air generates multiple reflections events. Such multiple events can mask primary events; thus from the interpretational viewpoint it is necessary to mitigate the multiples. In this manuscript we compare two methods of multiple attenuation: the predictive multichannel deconvolution (DPM) and the F-K filtering (FKF). DPM is based in the periodicity of the multiples while FKF is based in multiples and primaries splitting in F-K domain. DPM and FKF were applied in common-offset and CDP gathers, respectively. DPM is quite sensible to the correct identification of the period and size of the filter while FKF is quite sensible to an adequate choice of the velocity in order to split multiples and primaries events in the F-K domain. DPM is a method that is designed to act over a specific event. So, when the parameters are well selected, DPM is very efficient in removing the specified multiple. Then DPM can be optimized by applying it several times, each time with a different parameterization. A deficiency of DPM occurs when a multiple is superposed to a primary event: in this situation, DPM can attenuate also the primary event. On the other hand, FKF presents almost the same performance to all multiples that are localized in the same sector of the F-K domain. The two methods can be combined in order to take advantage of their associated potentials. In this situation, DPM is firstly applied, with a focus in the sea bed multiples. Then FKF is applied in order to attenuate the remaining multiples